Outcomes of endoscopic submucosal dissection for gastroesophageal reflux disease (ESD-G) for medication-refractory gastroesophageal reflux disease: 35 cases underwent ESD-G including 15 cases followed more than 5 years - Kazuhiro Ota (BMC, 2021)
Abstract Background Although some kinds of endoluminal surgery for patients with proton pump inhibitor (PPI)-refractory gastroesophageal reflux disease (GERD) have been reported, there are few reports on their long-term outcomes. In 2014, we reported the effectiveness of endoscopic surgery for PPI-refractory GERD, which we invented and named endoscopic submucosal dissection for GERD (ESD-G) in 2008. Thereafter, we accumulated more cases and monitored the patients’ condition postoperatively and describe the outcomes herein. Patients and methods This single-center, single-arm trial was conducted at the Osaka Medical and Pharmaceutical University Hospital. We compared outcomes between before and 3–6 months after ESD-G. Additionally, we investigated the outcomes of patients 5 or more years after ESD-G. Results We performed 42 ESD-G procedures in 35 patients between 2008 and 2020. In seven patients, ESD-G was performed twice for various reasons. The frequency scale for the symptoms of GERD score was significantly improved 3–6 months after ESD-G (22 → 10, p < 0.0001); the Los Angeles classification for reflux esophagitis was clearly improved after ESD-G (p = 0.0423). The number of reflux episodes was not decreased by ESD-G. There was a significant difference in the potency unit of gastric acid secretion suppressants for controlling GERD-related symptoms between baseline and 3–6 months after ESD-G (p = 0.0009). In patients without a history of distal gastrectomy who underwent ESD-G, the potency unit of gastric acid secretion suppressants significantly decreased 5 or more years after ESD-G (p = 0.0121). Conclusion ESD-G may be effective in patients with refractory GERD-related symptoms without a history of distal gastrectomy.